Open Versus Endoscopic Approach for Sinonasal Melanoma: A Systematic Review and Meta-analysis. Issue 2 (March 2019) - Hur, Kevin; Zhang, Paul; Yu, Alison; Kim-Orden, Natalie; Kysh, Lynn; Wrobel, Bozena
Background: Open resection (OR) of sinonasal mucosal melanoma (SNM) traditionally has been the gold standard for treatment. However, endoscopic resection (ER) has recently become a surgical alternative. The aim of this study was to compare survival outcomes between OR and ER of SNM. Methods: A literature search encompassing PubMed, Embase, Cochrane Library, Web of Science, ClinicalTrials.gov, and Google Scholar was performed. Two reviewers independently screened for original studies comparing survival outcomes between OR and ER for SNM. Data were systematically collected on study design, patient demographics, outcomes, and level of evidence. Quality assessment was performed using the Newcastle-Ottawa scale (NOS). Meta-analysis of overall survival and disease-free survival was performed using random-effects models. Results: The initial search yielded 2078 abstracts, of which 9 cohort studies were included for a total of 510 patients from 6 different countries. The average quality of all included studies using the NOS was 7.7 stars. Six out of 7 studies reported no differences in the stages of SNM between patients receiving ER versus OR. Overall survival was longer in the ER group versus OR group (hazard ratio [HR]: 0.68, 95% confidence interval [CI]: 0.49–0.95). There was no significant difference in disease-free survival between groups (HR: 0.59, 95% CI: 0.28–1.25). Conclusion: Based on the available literature, an endoscopic approach for SNM resection has survival outcomes that are similar or greater compared to an open approach.